ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK UMUM MILIK NEGARA DENGAN BANK UMUM MILIK SWASTA DI INDONESIA MENGGUNAKAN RASIO CAR, NPL, NIM, ROA, DAN LDR - B31111063, RYAN NOVELLA (Jurnal Manajemen Update, 2016)
Banking plays an important role in public life. Banking is a company in activities directly related to the community. Bank regarded as a driver of the economy of a country because it has a very vital function, then in this case the trust factor of the public is a major factor in conducting banking business. Good bank should be managed professionally so as to optimize the existing capital, loans targeted to prevent bad debts, as well as the benefit / profit from net interest generated. In this case the customers and prospective customers will consider the options before setting the type which banks will be selected. This study was conducted to better understand and know the level comparison of financial performance as measured by the ratio of CAR, NPL, NIM, ROA, and LDR between types of government bank ownership (SOEs) to private banks (BUMS). As has been described in previous studies sourced from Journal, Thesis and textbooks that these variables there are significant differences and the same (no difference), so here the author tries to discuss back but with the years and the data is different. The variables used in this research is Capital Adequacy Ratio (CAR) to measure capital adequacy, non-performing loan (NPL) to measure the amount of non-performing loans, net interest margin (NIM) to measure net interest income, return on assets (ROA) to measure the gain / loss, and Loan to Deposit Ratio (LDR) to measure lending. Sampling was done by purposive sampling method with the criteria listed in the Indonesia Stock Exchange and has a complete financial report last ten years. The study sample consisted of three state-owned banks (Bank Mandiri, Bank BNI, Bank BRI) and 3 BUMS Bank (Bank BCA, Bank Danamon, Bank Panin). Data were analyzed using descriptive and statistical analysis of different test Mann-Whitney test using SPSS version 16. This study shows the results of statistical tests that CAR is significant at 5%, the NPL ratio was significant at 5%, the ratio was not significant NIM, ROA was not significant at 10% (weak), and LDR significant.  Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Return on Assets (ROA), Loan to Deposit Ratio (LDR).